Estudo epidemiológico dos potenciais doadores de órgãos e tecidos por morte encefálica em Mato Grosso do Sul. - Karine Gomes Jarcem (2022)
The improvement of health technologies and practices increased the life expectancy of people affected by a diseased organ or tissue. Brazil invested in the provision of transplant services and became the second country in the world that most performs such procedures. The objective was to analyze the epidemiological aspects of potential donors (PD) of organs and tissues in brain death in the state of Mato Grosso do Sul state. It is an epidemiological study, with a quantitative approach, through a cross-sectional, descriptive, analytical, individualized design, on the PD of organs and tissues in a reference service for performing transplants in Campo Grande, capital of the state of Mato Grosso do Sul state. The research was carried out from June 2021 to March 2022, referring to patients attended by the service studied in a time frame of four years (2016 to 2019). The medical records of all patients were included from the opening record of the Brain Death (BD) protocols by the Organ Procurement Organization, with identification of the PD condition, over 18 years of age, of both sexes, regardless of the indicative medical diagnosis for opening the protocol. For qualitative variables, descriptive analysis was performed using absolute and relative frequency distributions, while for quantitative variables, descriptive statistics of measures of trend and data dispersion, such as minimum, maximum, mean and standard deviation values were used. In comparing the clinical profile of the PDs with the reasons for refusal, the chi-square statistical test was applied. For all tests applied, the significance level adopted was 5%. The research was previously approved by the Ethics Committee for Research with Human Beings of the institution, no. 4.605.747. During the study period, 476 Brain Death protocols were opened in PD, with 174 cases of refusal and 302 family interviews. Of those interviewed, 138 agreed with organ and tissue donation, with an annual average of 34.5 PD/year. 2.000 medical records were analyzed to identify PD from the diagnosis of death, with the identification of 70 PD records of organs and tissues in the period. Of the total analyzed, most (72.86%) were sex, aged over 50 years (57.14%), married (37.14%), with incomplete elementary education (59.27%) and hospitalized in the ICU (58.57%). The main medical diagnosis of PD was Hemorrhagic Stroke (50.00%), with a diagnosis of BD confirmed by transcranial Doppler imaging (91.05%). Most EM protocols (51.43%) were completed within 6 hours. Among the reasons for refusal, clinical refusals (42.65%) and family refusals (57.35%) stood out, with attention to the justification of maintaining an intact body (20.59%). Among the open BD protocols for PD of organs and tissues, most cases were discarded without the donation being carried out.